The Role of Village Funds to Improve Community Welfare: A Study in West Bandung Regency - Reni Wijayanti; Nur Imam Taufik (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: This study aims to determine the role of village funds in improving community welfare. Village funds are funds sourced from the APBN (State Budget and Expenditure) allocated to villages which are transferred through the district/city regional budget. According to applicable regulations, these funds must be used properly, such as to finance government administration, conduct development, community development, and empowerment. Design/methodology/approach: The research uses a quantitative descriptive research methods. Data collection was carried out by distributing questionnaires to several villages in West Bandung Regency and conducting interviews with related parties at the local Community Empowerment Service. Findings: The results of this study indicate that the management of village funds has an effect on improving community welfare. In general, the management of village funds in the West Bandung Regency has been managed in a transparent and accountable manner and involves community participation. Paper type: Research paper